Homologous Recombination Deficiency Score Determined by Genomic Instability in a Romanian Cohort - Viorica-Elena Rădoi; Mihaela Țurcan; Ovidiu Virgil Maioru; Andra Dan; Laurentiu Camil Bohîlțea; Elena Adriana Dumitrescu; Adelina Silvana Gheorghe; Dana Lucia Stănculeanu; Georgia Thodi; Yannis L. Loukas; Ileana-Delia Săbău (Diagnostics, 2023)
The Homologous Recombination Deficiency (HRD) Score, determined by evaluating genomic instability through the assessment of loss of heterozygosity (LOH), telomeric allelic imbalance (TAI), and large-scale state transitions (LST), serves as a crucial biomarker for identifying patients who might benefit from targeted therapies, such as PARP inhibitors (PARPi). This study aimed to investigate the efficacy of HRD testing in high-grade serous ovarian carcinoma, tubal, and peritoneal cancer patients who are negative for somatic BRCA1 and BRCA2 mutations and to evaluate the impact of HRD status on Bevacizumab and PARPi therapy response. A cohort of 100 Romanian female patients, aged 42–77, was initially selected. Among them, 30 patients had unsuitable samples for HRD testing due to insufficient tumor content or DNA integrity. Using the OncoScan C.N.V. platform, HRD testing was successfully performed on the remaining 70 patients, with 20 testing negative and 50 testing positive for HRD. Among the HRD-positive patients, 35 were eligible for and benefited from PARPi maintenance therapy, resulting in a median progression-free survival (PFS) increase from 4 months to 8.2 months. Our findings support the importance of HRD testing in ovarian cancer patients, demonstrating the potential therapeutic advantage of PARPi therapy in HRD-positive patients without somatic BRCA1/2 mutations.